2020
DOI: 10.1007/s10341-020-00483-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Identification of Apple Cultivars Based on Microsatellite DNA Analysis. I. The Database of 600 Validated Profiles

Abstract: Apple (Malus × domestica Borkh.) is the most widely grown permanent fruit crop of temperate climates. Although commercial apple growing is based on a small number of globally spread cultivars, its diversity is much larger and there are estimates about the existence of more than 10,000 documented varieties. The varietal diversity can be described and determined based on phenotypic characters of the external and internal traits of fruit, which, however, can be modulated by environmental factors. Consequently, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 53 publications
0
19
0
2
Order By: Relevance
“…In total, 219 apples of 22 cultivars were analyzed in this study and all cultivars were true to type, accurately identified using molecular tools [18]. The apple trees were grown in the experimental orchard of Laimburg Research Centre in Auer (Ora, Italy) at 220 m a.s.l.…”
Section: Fruits Samplesmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, 219 apples of 22 cultivars were analyzed in this study and all cultivars were true to type, accurately identified using molecular tools [18]. The apple trees were grown in the experimental orchard of Laimburg Research Centre in Auer (Ora, Italy) at 220 m a.s.l.…”
Section: Fruits Samplesmentioning
confidence: 99%
“…In this study, the different apple cultivars were categorized according to their phenotypic and commercial characteristics: old, commercial, and red-fleshed. Cultivars belonging to the old group originated between 1900 and 1950 according to Baric et al [18], but they have lost popularity and consumer acceptance mainly due to deficits in productivity, homogeneity, storability, and/or shelf life [19]. The commercial group gathers the most consumed apple varieties currently available on the world apple market.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Одним из часто используемых методов генотипирования сортов яблони, а также изучения их генетического разнообразия является метод SSR-(Simple Sequence Repeats)-маркирования, в основе которого лежит анализ вариабельности микросателлитных локусов генома. Поскольку на сегодняшний день для яблони известно значительное число микросателлитных маркеров с высоким уровнем полиморфизма (Liebhard et al, 2002;Silfverberg-Dilworth et al, 2006), данный метод успешно использовался при изучении генетического разнообразия и для генотипирования отечественных (Suprun et al, 2015;Kulikov et al, 2018;Pikunova et al, 2018) и зарубежных сортов яблони (Lassois et al, 2016;Pereira-Lorenzo et al, 2017;Baric et al, 2020).…”
Section: Introductionunclassified